'Give Me Women Wine and Snuff': A New Account of John Keats's Poem. (2nd July 2016) - Ghosh, Hrileena
Abstract: John Keats's short poem 'Give me women wine and snuff' dates from his years as a student at Guy's Hospital. Written on the cover of a fellow student's notebook, its six lines have routinely been dismissed by editors as 'Nonsense', 'Jocular' and 'Trivial'. This article gives an account of the poem in various editions of Keats, and offers the first accurate transcription of its original manuscript version. A close reading of it in the context of Keats's life and studies at Guy's reveals its witty and clear-sighted commentary on student life and on some of the gruesome rituals of the dissection room and what they reveal.